Near-infrared Fluorescent Imaging of Both Colorectal Cancer and Ureters Using a Low-Dose Integrin Targeted Probe - Verbeek, Floris P.R. (2014)
BACKGROUND: Irradical tumor resections and iatrogenic ureteral injury remain a significant problem during lower abdominal surgery. The aim of the current study was to intraoperatively identify both colorectal tumors and ureters in subcutaneous and orthotopic animal models using cRGD-ZW800-1 and NIR fluorescence. METHODS: The zwitterionic fluorophore ZW800-1 was conjugated to the tumor specific peptide cRGD (targeting integrins) and to the a-specific peptide cRAD. One nmol cRGD-ZW800-1, cRAD-ZW800-1, or ZW800-1 alone was injected in mice bearing subcutaneous HT-29 human colorectal tumors. Subsequently, cRGD-ZW800-1 was injected at dosages of 0.25 and 1 nmol in mice bearing orthotopic HT-29 tumors transfected with luciferase2. In vivo biodistribution and ureteral visualization were investigated in rats. Fluorescence was measured intraoperatively at several time points after probe administration using the FLARE imaging system. RESULTS: Both subcutaneous and orthotopic tumors could be clearly identified using cRGD-ZW800-1. A significantly higher signal-to-background ratio (SBR) was observed in mice injected with cRGD-ZW800-1 (2.42 ± 0.77) compared to mice injected with cRAD-ZW800-1 or ZW800-1 alone (1.21 ± 0.19 and 1.34 ± 0.19, respectively) when measured at 24 h after probe administration. The clearance of cRGD-ZW800-1 permitted visualization of the ureters and also generated minimal background fluorescence in the gastrointestinal tract. CONCLUSIONS: This study appears to be the first to demonstrate both clear tumor demarcation and ureteral visualization after a single intravenous injection of a targeted NIR fluorophore. As a low dose of cRGD-ZW800-1 provided clear tumor identification, clinical translation of these results should be possible.